PLACEMENT AND DELEGATION AND ITS EFFECT ON EMPLOYEE WORK DISCIPLINE AT SMA NEGERI 1 BELITANG MADANG RAYA OGAN KOMERING ULU TIMUR - Yansahrita Yansahrita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Delegation and placement are very important in the effort to implement good teaching and learning activities. This study aims to partially and jointly analyze the effect of placement, delegation of authority on employee work discipline and to analyze the most dominant variables in influencing employee work discipline at SMA NEGERI 1 Belitang Madang Raya Ogan Komering Ulu Timur, Results of regression analysis and correlation between placements. Work towards employee work discipline shows the regression model Y = 5.443 + 1.006X1 + e with a correlation coefficient of 0.880. The results of regression analysis and correlation between delegation of authority to employee work discipline show the regression model Y = 17.242 + 0.654X; + e with a correlation coefficient of 0.826. The results of multiple regression analysis and the correlation between job placement and delegation of authority jointly with job discipline show the regression model Y = 5.309 + 0.683X / + 0.292X2 + e with a correlation coefficient of 0.911 at the 95% confidence level, it is obtained the notion that the placement and delegation of authority are simultaneously can predict employee work discipline. Job placement and delegation of authority simultaneously have a positive influence which is quite close with work discipline of 81.5% and has a significant effect. This research was conducted on 25 respondents with the analytical method used is path analysis using SPSS software. Keywords: Delegation of Authority, Placement, Work Discipline